The Carrying Capacity of Infrastructure and Spatial Planning to the Recovery of Pandan Beach Natural Tourism Due to the Covid-19 Pandemic in North Sumatra (Central Tapanuli Regency Case Study) - Fernando Raja Partogi Sibagariang; Agus Purwoko (Konfrontasi: Jurnal Kultural, Ekonomi dan Perubahan Sosial, 2021)
The purpose of this research is: (1) know the carrying capacity of infrastructure for the recovery and development of natural attractions on the pandan beach of Central Tapanuli Regency, (2) analyze the suitability of spatial arrangements in the Regency towards the recovery and development of natural attractions on pandan beaches of Central Tapanuli Regency, (3) analyze the priority of handling infrastructure and spatial arrangement policies for the acceleration of recovery and development of natural attractions on pandan beaches. Central Tapanuli. The research method used is to use descriptive qualitative methods with case study models. Data collection techniques with interviews and documentation. The results of this study, that is (1) The carrying capacity of central Tapanuli Regency infrastructure to the recovery and development of natural attractions on pandan beach, already has infrastructure such as transportation, economy, health and social. (2) The suitability of spatial arrangements in the Regency to the recovery and development of natural attractions on pandan beach, namely when viewed from the distribution of facilities and infrastructure and the distribution of tourism attractions the most influential space functions due to the covid-19 pandemic are restaurants or restaurants and lodgings or hotels. (3) Priority of handling infrastructure and spatial arrangement policy for the acceleration of recovery and development of natural attractions on pandan beaches of Central Tapanuli Regency, namely the economy. Whether it's a small or medium-sized business or a large scale.